Deterioration of concrete under the coupling effects of freeze–thaw cycles and other actions: A review. (14th February 2022) - Wang, Ruijun; Zhang, Qingjun; Li, Yang
Highlights: The mechanisms that lead to concrete deterioration due to the coupling effects of freeze–thaw (FT) cycles and other actions were discussed. The influence of the combination of FT cycles with other actions on the properties of concrete was reviewed. Methods for mitigating concrete deterioration were summarized. Gaps and limitations in research on concrete deterioration due to the influence of coupled actions were discussed. Abstract: In cold regions, the action of freeze–thaw (FT) cycles is regarded as the main cause of concrete deterioration. The coupling actions between FT cycles and chemical actions, such as chloride penetration, sulfate attack, carbonation and alkali–silica reaction cannot be ignored because the combination of different degradation processes may be more severe than that of processes acting separately. The synergetic effects between different physical degradation processes must also be considered. This paper reviews the mechanisms that lead to concrete deterioration due to the coupling action of FT cycles and other factors. The coupling action causes more serious damage to concrete than a single action. Chemical actions have both positive and negative effects on FT cycles, whereas physical actions such as external loading, salt crystallization, and wetting–drying cycles only aggravate FT damage. The physical and mechanical properties of concrete under synergistic actions are discussed and analysed. The loss of physical and mechanical properties of concrete is related to the type and concentration of the chemical solution, as well as to the load stress ratio. Protocols to mitigate concrete deterioration are also reviewed, such as the use of air-entraining agents, the incorporation of fibers and the replacement of cement with pozzolanic cementitious materials.